Morphological Observation on Longidorus crassus Thorne, 1974 (Nematoda: Longidoridae) and Its Intraspecies Variation - Ye, Weimin (Society of Nematologists, 2005)
Longidorus crassus is a common species and widely distributed in Arkansas. It was also identified for the first time in samples from Alabama, Iowa, Kansas, Nebraska, South Carolina, Wisconsin, and Canada. It is a parthenogenetic species, but a few males were found and were described herein for the first time. Four developmental juvenile stages were identified. A high degree of intraspecies variation was observed among different populations of this species. Twenty-three populations of L. crassus found in Arkansas were studied for their variability using standard measurements, mean comparison, and coefficient of variation. Most of the Arkansas populations have a smaller body than the paralectotypes. Populations Long-63 and Long-88 are close to the paralectotype population. Two populations, Long-10 and Long-80, are different from each other and all other populations. The majority of morphometric characters of this species do not have a normal distribution pattern as they have a high degree of variability within and between populations. The means of many morphometric characters strikingly differ between populations. Hierarchical cluster analysis based on female morphometric character means including body length, distance from vulva opening to anterior end, head width, odontostyle length, esophagus length, body width, tail length, and anal body width were used to examine the morphometric relationships and create dendrograms for 23 Arkansas populations and the lectotype population.